Waste wood block as partial coarse aggregate replacement in reinforced concrete beam - Lee, Chun Hoong (2016)
Most of the solid waste materials are not properly managed and cause pollution to this earth. In addition, the use of natural aggregate in construction lead to huge quarrying activities. Hence, by recycling the waste materials to replace the coarse aggregate can assist to lower the environmental impact. Performance of concrete properties possessing wood block as partial replacement of coarse aggregate were presented in this study. All the wood block were immersed into water before mixing with concrete to avoid it from soaking up the water required during mixing process. Thirty six cube specimens and four beam specimens were prepared. The concrete mix was casted according to the concrete mix design with different replacement contents of the wood block, which are 3%, 6% and 9% respectively. Test for hardened concrete properties including concrete density, compressive strength and flexural test were conducted. The concrete density decreased as the percentage of wood block increased. At the same time, as the wood aggregate content was increased, the compressive strength was decreased. For flexural test, the concrete beam containing 3% of wood aggregate able to sustain maximum load and perform smaller deflection compared to the other replacement beams. This study indicated that the wood aggregate was suitable to replace the coarse aggregate and the 3% of wood block was found as the best content of this study for replacement as the compressive strength was higher than control concrete and the flexural behaviour was closed to conventional concrete.